Verbal creative category in comparison to the category of aspect and activity result - Ejsmunt-Wieczorek, Izabela (Papers in Linguistics, 2019)
The article is a voice in the polemics of linguists that have been going on for years, concerning the lack of clarity of boundaries between word-formation categories and the related deficit of consequences in the form of overlapping ranges of meaning of semantic groups.. An example of such semantic lability is the creative verbal category, which in comparison with the aspect function and with reference to the class of effective verbs, seems to be an unnecessary repetition. The question about the meaning of creating a creative category will be considered based on contemporary national material, as well as in reference to examples from historical and dialectal Polish.